A compilation of igneous rock volumes at volcanic passive continental margins from interpreted seismic profiles. (December 2020) - Gallahue, Molly M.; Stein, Seth; Stein, Carol A.; Jurdy, Donna; Barklage, Mitchell; Rooney, Tyrone O.
Abstract: The rifting and breakup of continents, and subsequent seafloor spreading, give rise to passive continental margins, many of which are underlain by enormous volumes of igneous rocks and termed volcanic passive margins. The relationships between the igneous rocks, rifting, and mantle plumes remain unresolved despite extensive studies and proposed alternative models. To support such studies, we use published, previously interpreted, seismic reflection and refraction data to compile a dataset of igneous rock volumes and geometries at volcanic passive continental margins. The VOLMIR (VOLcanic passive Margin Igneous Rocks) dataset is based on margin-crossing profiles on which the volumes and geometries of both shallow seaward dipping reflector (SDR) and deeper high velocity lower crustal (HVLC) units can be measured. It includes information about the ages of continental breakup, and profile distances from the associated Euler pole and from hotspots that may have played roles in the breakup process. Despite local variations, the dataset shows general patterns. The average ratio of SDR to HVLC volumes, 0.3–0.4, is relatively consistent between profiles, implying that formation of these units is related during continental breakup. The volumes of igneous rocks display a moderate positive correlation with distances from the Euler pole, but only a weak negative correlation with distances from the nearest hotspot (at the time of margin formation), suggesting that in continental breakup lithospheric processes (passive rifting) have greater effects than hotspots (active rifting). These results suggest that this dataset will be useful for exploring aspects of the rifting process, relationships between volcanic rifted margins, and potential explanations for their similarities and differences. Highlights: We present a dataset of SDR and HVLC unit volumes at volcanic passive margins. The average ratio of SDR to HVLC volumes, 0.3–0.4, is relatively consistent. The consistent ratio implies that these units form jointly. SDR volumes vary with distance from the associated Euler pole and hotspot. The variations suggest passive rifting processes have greater effects than active.